Enhancing Natural Resource Programs: Designing Effective Brochures - Martha C. Monroe; Ludovica Weaver (EDIS)
Circular 1436, a 14-page illustrated circular by Martha C. Monroe and Ludovica Weaver, provides the basic concepts of design for the beginning brochure designer. Includes references. Published by the UF School of Forest Resources and Conservation, April 2007.